ETUDE PROTECTION DE L’AEROPORT D’EL BAYADH CONTRE LES INONDATIONS - Haithem Yahia; Salah Eddine Sabri (My University, 2025)
This study focuses on the flood risk threatening the city of El Bayadh, particularly the airport area, due to the floods of the Oued Defla. It aims to propose a protection channel with optimal dimensions to reduce the future impact of flooding, based on a thorough analysis of the geographical, hydrological, and hydraulic characteristics of the region. The methodology includes a general diagnosis of the phenomenon in Algeria, a detailed description of the site, a historical analysis of major floods—especially the October 2011 flood—and hydrological and hydraulic studies to design the protection channel. The results provide a scientific and technical foundation to guide development projects aimed at protecting the city and its critical infrastructures. ------------------------------------------------------------------------- تتناول هذه الدراسة مشكلة الفيضانات في مدينة البيض، خصوصًا بمنطقة المطار المتأثرة بوادي الدفة. تهدف الدراسة إلى تصميم قناة حماية بأبعاد مناسبة للحد من أضرار الفيضانات المستقبلية، عبر دراسة معمقة للظروف الجغرافية والهيدرولوجية والهيدروليكية للمنطقة. اعتمدت الدراسة على تحليل تاريخي لأبرز الفيضانات، خاصة فيضان أكتوبر 2011، إلى جانب حساب التدفقات القصوى وتصميم القناة باستخدام نماذج رياضية. تشكل نتائج الدراسة قاعدة علمية وتقنية لدعم مشاريع حماية المدينة وتأمين منشآتها الحيوية. ------------------------------------------------------------------------- Cette étude porte sur le risque d’inondations menaçant la ville d’El Bayadh, en particulier la zone de l’aéroport, à cause des crues de l’oued Defla. Elle vise à proposer un canal de protection aux dimensions optimales pour réduire l’impact futur des inondations, grâce à une analyse approfondie des caractéristiques géographiques, hydrologiques et hydrauliques de la région. La méthodologie comprend un diagnostic général du phénomène en Algérie, une description détaillée du site, une analyse historique des crues majeures, notamment celle d’octobre 2011, ainsi que des études hydrologiques et hydrauliques permettant de dimensionner le canal de protection. Les résultats fournissent une base scientifique et technique pour orienter les projets d’aménagement visant à protéger la ville et ses infrastructures essentielles.
Keywords: Flood; Oued Defla; protection channel; hydrology; hydraulics; El Bayadh city; natural hazard.: فيضان، واد الدفة، قناة الحماية، الهيدرولوجيا، الهيدروليكا، مدينة البيض، خطر طبيعي; Inondation; canal de protection; hydrologie; hydraulique; ville d’El Bayadh; risque naturel.